Transport properties of a three-shell icosahedral matryoshka cluster: a first-principles study. Issue 21 (23rd February 2017) - Zhang, Lu; Huang, Jing; Wang, Weiyi; Li, Qunxiang; Yang, Jinlong
Abstract : The molecular junction based on three-shell icosahedral matryoshka cluster with huge magnetic moment exhibits robust spin-filtering effect, which highlights it for promising applications in molecular devices. Abstract : Extensive efforts have been devoted to explore transport behaviors through various molecules and clusters, which are promising building blocks in molecular electronics. Here, we examine the spin-polarized electronic structures and transport properties of a three-shell icosahedral matryoshka cluster, Pb@Mn12 @Pb20, by performing density functional theory calculations combining with non-equilibrium Green's function method. Theoretical results clearly reveal that, twelve Mn atoms in the middle layer anti-ferromagnetically couple with the center Pb atom and Pb atoms in the outlayer, while the Pb@Mn12 @Pb20 cluster still has a huge magnetic moment of 28.0 bohr magneton, mainly contributed by these Mn atoms. The calculated spin-resolved transmission spectra of the proposed Pb@Mn12 @Pb20 junctions exhibit robust spin filtering effect, which is not sensitive to the anchoring distance and the adopted electrode materials, and the conductance through the cluster under the small bias voltage is mainly determined by the spin-up electrons. These findings indicate that this kind of three-shell matryoshka cluster with huge magnetic moment holds potential applications in molecular spintronic devices.